2016
DOI: 10.1161/circheartfailure.115.002593
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response to Low-Dose Dopamine or Low-Dose Nesiritide in Acute Heart Failure With Reduced or Preserved Ejection Fraction

Abstract: BACKGROUND The Renal Optimization Strategies Evaluation in Acute Heart Failure (ROSE AHF) trial found that as compared to placebo, neither low-dose dopamine (2 ug/kg/min) nor low-dose nesiritide (0.005 µg/kg/min without bolus) enhanced decongestion or preserved renal function in AHF patients with renal dysfunction. However, there may be differential responses to vasoactive agents in AHF patients with reduced versus preserved ejection fraction (EF). This post-hoc analysis examined potential interaction between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 29 publications
(38 reference statements)
2
29
0
Order By: Relevance
“…A post hoc subgroup analysis suggested that the effects of low dose dopamine differed by heart failure subtype; in patients with heart failure with reduced ejection fraction dopamine may have enhanced decongestion and improved prognosis, providing an impetus to further study. 41 …”
Section: Introductionmentioning
confidence: 99%
“…A post hoc subgroup analysis suggested that the effects of low dose dopamine differed by heart failure subtype; in patients with heart failure with reduced ejection fraction dopamine may have enhanced decongestion and improved prognosis, providing an impetus to further study. 41 …”
Section: Introductionmentioning
confidence: 99%
“…Our study also suggests a rather inappropriate use of inotropes and/or vasopressors, as only a small proportion of patients treated with catecholamines presented with cardiogenic shock and less than half had signs of peripheral hypoperfusion. Despite the widespread use of inotropes, data from controlled trials have failed to demonstrate benefit with these agents . On the contrary, catecholamines have been associated with increased risk for adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Specific areas of interest can be found in Table 2, but common markers include myocardial injury, fluid overload and kidney enlargement [1]. [31][32][33].…”
Section: Risk Factors and Diagnosismentioning
confidence: 99%
“…A stepwise algorithm directed at 24-h urine volume containing furosemide with or without metolazone resulted in an improvement in renal function compared with standard diuretic therapy [1]. The effects of low-dose dopamine, nesiritide, or placebo on decongestion and renal function were compared by ROSE-AHF [33]. No significant differences in the incidence of type 1 CRS were observed in patients' symptoms or change in renal function.…”
Section: Risk Factors and Diagnosismentioning
confidence: 99%